POLA PERILAKU DAN PEMETAAN AKTIVITAS PENGUNJUNG MUSEUM SONOBUDOYO YOGYAKARTA - Fariz Nizar; Naufal Kresna Diwangkara (Vastutara : Arsitektur, Digital, Sejarah, Struktur dan Lingkungan, 2025)
The Sonobudoyo Museum was previously a foundation in the field of Javanese, Balinese, Lombok and Madurese culture which was founded in 1919 in Surakarta as the Java Instituut, then this museum changed its name to the Sonobudoyo Museum which was inaugurated by Sri Sultan Hamengkubuwana VIII. In this research, the researcher was interested in observing the Sonobudyo museum. Here the researcher conducted research on behavior patterns and activity mapping or often called Behavior Mapping at the Sonobudoyo museum. Here researchers look at the movement of visitors in the museum area in order to find out the locations and spots frequently visited (Centers of Attention) by local and foreign tourists. This research aims to look for Points of Interest in the layout and layout of the Sonobudoyo building. This research uses qualitative research methods by making observations by observing in the field and seeing the movements of visitors directly. The researcher observes the direct movements of visitors by taking notes and taking photos in the field. The results of this research are personal space, territory, privacy and spatial settings in the museum, which can be seen from the movement and accessibility in the Sonobudoyo museum.